The importance of rapid strep test for acute tonsillopharyngitis in children with pharyngeal deposits - S.A. Tsar'kova; A.S. Sokolova; V.P. Vavilova (LCC «Medicine-Inform», 2020)
S.A. Tsar'kova1, A.S. Sokolova2, V.P. Vavilova3 1Ural State Medical University, Yekaterinburg, Russian Federation 2Children's City Clinical Hospital No. 11, Yekaterinburg, Russian Federation 3Kemerovo State Medical University, Kemerovo, Russian Federation Aim: to assess the management of children with acute tonsillopharyngitis according to practice guidelines and the importance of rapid strep test. Patients and Methods: prospective non-interventional study was performed to analyze whether management strategy for children with pharyngeal deposits matches practice guidelines. Pediatricians were provided an opportunity to perform rapid strep test in children with pharyngeal deposits using Streptatest. Children older than 1 year who visited pediatrician or emergency unit or were admitted to hospital for pharyngeal deposits were enrolled in the study. Inclusion criteria was the possibility to follow-up a child till completing case of disease. Results: initial examination using rapid strep test was performed in 215 children. All children were diagnosed with moderate acute tonsillopharyngitis. The children were subdivided in two groups by age according to the management algorithm for children with pharyngeal deposits addressed in Federal practice guidelines of the Union of Pediatricians of Russia, i.e., 2.3±0.7 years (n=45, 20.9%) and 8.5±4.1 years (n=170 , 79.1%). Streptococcal etiology was verified in 31 of 215 children (14.4%). In 8.9% of children under 3 years of age, acute tonsillopharyngitis was caused by group A β-hemolytic streptococcus (group A strep). No pathognomonic signs of acute tonsillopharyngitis caused by group A strep were revealed. The use of Streptatest at early stages of etiological diagnostics reduced unreasonable prescription of antibiotics by 74%. Prevented economic damage associated with rapid strep test use to diagnose acute tonsillopharyngitis was estimated at 55,791 RUB. As a result, the costs of the treatment for one case of acute tonsillopharyngitis were reduced by 410 RUB. Conclusion: Streptatest reduces the percentage of unreasonable prescription of antibiotics for acute tonsillopharyngitis in children and prevents economic damage. Keywords: acute tonsillopharyngitis, group A β-hemolytic streptococcus, antibiotic, antibacterial therapy, resistance, Streptatest, rapid strep test, immunoassay. For citation: Tsar'kova S.A., Sokolova A.S., Vavilova V.P. The importance of rapid strep test for acute tonsillopharyngitis in children with pharyngeal deposits. Russian Journal of Woman and Child Health. 2020;3(2):112-118. DOI: 10.32364/2618-8430-2020-3-2-112-118.